Germany's Bundesliga : does money score goals? - Schmedders, Karl, (SAGE knowledge. Cases., 2016)
During one of the most nerve-wracking football matches of the 2012-2013 Bundesliga season, life-long friends Franz Dully and Max Vogel begin arguing about whether the wealth of a football club determines its success during the season. In order to disprove Vogel's claim that 'money scores goals,' Dully must analyze the Bundesliga's current market values, points earned, and mid-season leader data.